Guidelines for transferring sustainable urban logistics concepts - Leon Klose; Anne Beckmann; Stephanie Ihlenburg; Raphael Preindl; Frank Straube (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Inner-city freight transports are characterized by numerous deficits, such as congested infrastructure and increasing emission and noise levels. Sustainable urban logistics is a field with many concepts to improve the efficiency and sustainability of these transports. However, guidelines how to transfer and implement successful concepts in other cities are missing. Methodology: We follow a multi-method approach using a systematic literature review, a multi case study analysis and expert interviews. Findings: First, we identify and characterize 16 concepts of urban logistics. Additionally, seven profiles for typical urban areas are developed based on important factors influencing urban logistics. Second, 137 projects in 70 cities are analyzed. The concepts of urban logistics are aggregated to three urban logistics systems. Their fit with typical urban areas is evaluated. Finally, the findings are assessed with expert interviews and a framework for transferring sustainable urban logistics concepts to other cities is proposed. Originality: The adaptation of urban logistics concepts to specific local environments receives little attention in the literature. By proposing a framework for the transfer of sustainable urban logistics systems, this paper integrates the knowledge gained in urban logistics projects in many cities. Future projects may benefit from a faster and more efficient successful implementation.
urn:nbn:de:gbv:830-882.0200739; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; City Logistics